Behavioral abnormalities in the Fmr1‐KO2 mouse model of fragile X syndrome: The relevance of early life phases. Issue 10 (7th June 2017) - Gaudissard, Julie; Ginger, Melanie; Premoli, Marika; Memo, Maurizio; Frick, Andreas; Pietropaolo, Susanna
Abstract : Fragile X syndrome (FXS) is a developmental disorder caused by a mutation in the X‐linked FMR1 gene, coding for the FMRP protein which is largely involved in synaptic function. FXS patients present several behavioral abnormalities, including hyperactivity, anxiety, sensory hyper‐responsiveness, and cognitive deficits. Autistic symptoms, e.g., altered social interaction and communication, are also often observed: FXS is indeed the most common monogenic cause of autism. Mouse models of FXS are therefore of great interest for research on both FXS and autistic pathologies. The Fmr1‐KO2 mouse line is the most recent FXS model, widely used for brain studies; surprisingly, little is known about the face validity of this model, i.e., its FXS‐like behavioral phenotype. Furthermore, no data are available for the age‐related expression of the pathological phenotypes in this mouse line, a critical issue for modelling neurodevelopmental disorders. Here we performed an extensive behavioral characterization of the KO2 model at infancy, adolescent and adult ages. Hyperactivity, altered emotionality, sensory hyper‐responsiveness and memory deficits were already present in KO mice at adolescence and remained evident at adulthood. Alterations in social behaviors were instead observed only in young KO animals: during the first 2 weeks of life, KOs emitted longer ultrasonic vocalizations compared to their WT littermates and as adolescents they displayed more aggressive behaviors towards a conspecific. These results strongly support the face validity of the KO2 mouse as a model for FXS, at the same time demonstrating that its ability to recapitulate social autistic‐relevant phenotypes depends on early testing ages. Autism Res 2017, 10: 1584–1596 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.